Isotype : design and contexts 1925-1971 - Burke, Christopher; Kindel, Eric; Walker, Sue (London : Hyphen, 2013)
The work in graphic communication carried out by Otto Neurath and his associates – now commonly known simply as Isotype – has been the subject of much interest in recent years. Conceived and developed in the 1920s as ‘the Vienna method of pictorial statistics’, this approach to designing information had from its inception the power to grow and spread internationally. Political developments in Europe played their part in its development, and production moved to the Netherlands (1934) and to England (1940), where the Isotype Institute continued to produce work until 1971. Bringing together the latest research, this book is the first comprehensive, detailed account of its subject. The Austrian, Dutch, and English years of Isotype are described here freshly and extensively. There are chapters on the notable extensions of Isotype to Soviet Russia, the USA, and Africa. Isotype work in film and in designing for children is fully documented and discussed. Between these main chapters the book presents interludes documenting Isotype production visually. Three appendices reprint key documents. In its international coverage and its extensions into the wider terrain of history, this book opens a new vista in graphic design.
boek